A retrospective study of direct cost to patients associated with the use of oral oncology medications for the treatment of multiple myeloma. (2nd April 2016) - Lee, Claire; Grigorian, Matthew; Nolan, Ryan; Binder, Gary; Rice, Gary
Abstract: Objective: To examine direct cost to patients associated with oral oncolytics for the management of multiple myeloma (MM) both before and after financial assistance, and assess the effect on adherence. Methods: In this retrospective study, pharmacy claims were analyzed for those patients with a diagnosis of MM who received thalidomide, lenalidomide, or pomalidomide from a large specialty pharmacy in the US between January 1, 2011, and December 31, 2013. Average direct cost to patients, per prescription, was analyzed both before and after financial assistance. Adherence was assessed through an analysis of medication possession ratio (MPR) for those patients who filled a prescription ≥2 times throughout the 3-year time period. Results: A total of 77, 821 prescriptions for thalidomide, lenalidomide, and pomalidomide were filled by 6731 unique patients between January 1, 2011, and, December 31, 2013. The average direct cost to patients, per prescription, for any of these three agents was $227.23 prior to financial assistance and $80.11 after financial assistance, representing an average patient savings of $147.14 per prescription. Prior to financial assistance, the average direct cost to patients was ≤$50 for 57.6% of all prescriptions. After financial assistance, 86.2% of patients had a direct cost of ≤$50 per prescription. Adherence, as assessed by MPR, did not vary significantly based on direct cost to the patient. Limitations: This study included patients receiving therapy from a single specialty pharmacy for a single indication. There may be patients included in the analysis who received prescriptions from other pharmacies prior to or after the prescriptions available for analysis. Most of the prescriptions included in the analysis were for lenalidomide. Conclusions: This retrospective study demonstrated that the specialty pharmacy helped patients significantly reduce their direct cost expenditures by securing funding and co-pay assistance.